Polyimide enameled wire and preparation method thereof
By introducing BeO particles and AlN powder into the polyimide paint layer, the thermal conductivity and electrical insulation performance of the enameled wire are improved, and the problem of insufficient heat resistance of traditional enameled wires in high temperature environments is solved, which extends the service life and improves the Equipment performance.
Patent Information
- Application Number
- CN202510018333.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-02-11
AI Technical Summary
Traditional enameled wires are insufficient heat resistance in high temperature environments, resulting in a decrease in the material's dielectric constant and breakdown voltage, increasing the risk of leakage current, and low thermal conductivity affects the heat dissipation performance of the insulating coating, limiting the improvement of equipment performance.
The polyimide paint layer was prepared by heating curing with polyamic acid solution containing BeO particles and AlN powder, which significantly improved the thermal conductivity and electrical insulation properties of the polyimide.
It significantly improves the heat dissipation and electrical insulation performance of the enameled wire, prevents performance degradation or damage caused by overheating in high temperature environments, extends the service life of the enameled wire, and improves the overall efficiency and reliability of the equipment.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of enameled wires, and in particular to a polyimide enameled wire and a preparation method thereof. Background Art
[0002] With the rapid development of modern industry and electronic technology, the demand for high-performance electrical equipment is increasing. Traditional enameled wires usually use polyethylene (PE), polyvinyl chloride (PVC), polyester or ordinary polyimide as insulating coating materials, but under high temperature conditions (such as over 200°C), the heat resistance of the above materials is obviously insufficient. In applications such as high-power motors, transformers, aerospace, military equipment, etc., the equipment often needs to operate stably for a long time in a high-temperature environment. Traditional enameled wires can no longer meet the increasingly stringent working environment requirements. For example, the operating temperature of the windings in aircraft engines may exceed 300°C, and the drive motors of electric vehicles will also generate a lot of heat when running at high speeds. At the same time, as the temperature rises, the dielectric constant and breakdown voltage of traditional enameled wire materials will gradually decrease, resulting in increased leakage current and even breakdown. At the same time, traditional enameled wire coating materials usually have low thermal conductivity. The thermal conductivity of polyethylene is about 0.35~0.5W / m·K, the thermal conductivity of polyvinyl chloride is about 0.15~0.2W / m·K, the thermal conductivity of polyester is about 0.2~0.3W / m·K, and the thermal conductivity of ordinary polyimide is about 0.2~0.4W / m·K. They cannot effectively conduct heat, which greatly affects the heat dissipation performance of the insulating coating. In high-power equipment, a large amount of heat is generated when current passes through the conductor. Especially in high-power and high-current application scenarios, the heat dissipation problem is particularly prominent. The low thermal conductivity of traditional enameled wire has become a key bottleneck limiting the improvement of equipment performance. With the development of industrial automation and intelligence, higher requirements are placed on the heat resistance, insulation and thermal conductivity of enameled wire.
[0003] In order to overcome the limitations of traditional enameled wires, researchers began to explore the application of new materials. Polyimide, as a high-performance polymer, has excellent heat resistance, mechanical strength and electrical insulation properties, and has gradually become the first choice for enameled wire coating materials. However, ordinary polyimide still has the problem of poor thermal conductivity, which makes it difficult to meet the needs of efficient heat dissipation. Therefore, researchers have introduced inorganic fillers (such as aluminum oxide, silicon carbide, aluminum nitride, graphene, etc.) to improve the thermal conductivity of polyimide while maintaining its excellent heat resistance and insulation. For example, CN117659858A discloses an enameled wire varnish material based on graphene enhanced heat dissipation, and the enameled wire varnish material includes the following components in parts by weight: 50 to 70 parts of modified polyimide resin; 1 to 5 parts of modified graphene sheets; 5 to 15 parts of aluminum oxide; 5 to 10 parts of thermal stabilizer; 5 to 10 parts of antioxidant; 0.1 to 5 parts of boron nitride. The high strength and good flexibility of graphene make the enameled wire more stable when subjected to mechanical stress, reducing the risk of damage during manufacturing and use. Precise control of the spacing between graphene sheets helps to form a more effective heat conduction network. Proper adjustment of the spacing between layers can maximize the efficiency of heat transfer between graphene layers, thereby improving the overall heat dissipation performance of the enameled wire. CN115810449A discloses a highly efficient heat dissipation enameled flat wire and its production process, the steps of which include extrusion processing, softening treatment, four-pass paint-scraping die painting treatment, temperature control baking and finished product winding, the four-pass paint-scraping die painting treatment includes the following steps: (1) polyester imide paint, aromatic modified polyimide, epoxy resin, polyethersulfone dispersion and graphene oxide dispersion are mixed in a mass ratio of 1: (1.2~1.6): (0.3~0.5): (0.5~0.7): (2~3) to obtain paint; (2) using an enameled wire painting movable mold to evenly apply the paint on the surface of the softened copper wire, and perform four-pass paint-scraping die painting treatment. The present application uses graphene oxide dispersion and polyethersulfone dispersion, and the two work together to improve the heat dissipation performance of the enameled flat wire. The use of a tetrafunctional epoxy resin and a TT310 trifunctional epoxy resin with high crosslinking density and aromatic density as epoxy resin can further improve the heat dissipation performance of the enameled flat wire. CN116313274A discloses a high thermal conductivity insulating copper flat wire for a 10kV high voltage motor, which is composed of a flat copper conductor and an insulating layer, wherein the insulating layer is composed of a high thermal conductivity polyesterimide lacquer layer and a high thermal conductivity polyimide film reinforced low-resin mica tape sheathing layer from the inside to the outside; wherein the composition of the high thermal conductivity polyesterimide lacquer layer includes polyesterimide wire lacquer and high thermal conductivity filler; the structure of the high thermal conductivity polyimide film reinforced low-resin mica tape sheathing layer is to cover a layer of high thermal conductivity epoxy adhesive containing high thermal conductivity filler on the polyimide film surface of the polyimide film powder mica tape; the high thermal conductivity insulating copper flat wire of the present invention has good insulation, thermal conductivity and heat resistance, and is suitable for use in 10kV high voltage motors.The surface insulation layer of the copper flat wire exhibits high thermal conductivity, with a thermal conductivity coefficient of ≥0.5W / m·k. In addition, some people have improved the structure of the enameled wire. For example, CN104934145A discloses a cooling system for the enameled wire, including a cooling air duct arranged along the line direction of the enameled wire, a cooling fan connected to the cooling air duct is arranged outside the cooling air duct, the cooling air duct includes a front side plate and a rear side plate arranged parallel to each other, a cooling water pipe is arranged on the front side plate, and the arrangement of the folding plate in the air duct enables the folded wind shield on the folding plate to reflect the cooling wind, blow the cooling wind to both sides of the enameled wire, and accelerate the cooling effect of the enameled wire. CN208298569U discloses a fast heat dissipation enameled stranded wire, including an aluminum wire core, a high temperature resistant elastic buffer layer, a first copper round wire layer, a second high temperature resistant elastic buffer layer and a second copper round wire layer are sequentially arranged outside the aluminum wire core; the aluminum wire core includes a plurality of twisted aluminum round wires, and an aromatic polyimide paint layer, a first tear-resistant glass fiber layer, an insulating paint layer, a second tear-resistant glass fiber layer, a nylon paint layer and an adhesive paint layer are arranged outside the aluminum round wire; heat dissipation channels are arranged on the inner and outer walls of the high temperature resistant elastic buffer layer and the second high temperature resistant elastic buffer layer. The elastic buffer layer enables it to dissipate heat independently and improves the heat dissipation speed, and the heat dissipation channels arranged at the same time can accelerate the flow of heat and improve the heat dissipation rate. CN205900174U discloses an enameled wire with a heat dissipation function, comprising an enameled outer layer, a conductor inner core and a heat dissipation layer, wherein an aluminum alloy mesh layer is arranged in the heat dissipation layer, and heat dissipation micropores are arranged in the heat dissipation layer. The enameled outer layer comprises an epoxy resin base layer, a polyurethane coating layer is arranged on the outside of the epoxy resin base layer, and a polyimide coating layer is arranged on the outside of the polyurethane coating layer. The heat generated by the enameled wire during operation can be well dissipated, and the aluminum alloy mesh layer has good heat conduction, which ensures that the enameled wire can maintain a stable working temperature during long-term use, and greatly reduces the loss of the enameled wire caused by high temperature. CN111326287B discloses a 220-grade polyimide enameled copper round wire, including a paint layer arranged on the outer wall of the copper wire, a plurality of convex paint blocks are arranged on the outer side of the paint layer, and a plurality of intermediate paint layers are arranged between the copper wire and the paint layer, and the convex paint blocks can support continuous and interlinked micro-gaps, and the micro-gaps do not affect the normal conduction of the enameled wire, and during the high-speed rotation of the motor, the air can flow inside the motor, and a small part of the air can also flow between the micro-gaps, so as to effectively take away the heat generated when the enameled wire is energized, effectively avoiding the accumulation of heat and improving the overall heat dissipation effect. CN102385957A discloses a method for manufacturing a heat dissipating enameled wire, including the following steps: A, coating one or several layers of insulating paint on the surface of the enameled copper wire; B, coating one or several layers of heat dissipation layer on the insulating paint layer, and the heat dissipation layer is a mixture of conductive material and insulating paint.In the process of winding the enameled wire, gaps between the wires are formed to form heat dissipation particles and make the wires breathable. The heat dissipation layer of the enameled wire also produces a pore effect by adding a graphitized mesoporous breathable structural material to the polymer, which can quickly dissipate heat and has the effect of quickly dissipating heat.
[0004] Although the introduction of the above-mentioned composite materials or new structures has improved the heat resistance or service life of the enameled wire to a certain extent, the setting of the complex enameled wire structure or the heat dissipation cooling structure requires a large space and cannot be well applied in the current miniaturization and high power background. Although the introduction of thermally conductive inorganic fillers can improve the heat dissipation effect of polyimide, it usually has high hardness and rigidity. When the content is high, the poor compatibility between the filler and the polyimide matrix easily causes the enameled wire to break or peel off during bending, stretching or vibration, affecting its service life and reliability. Non-intrinsic silicon carbide, graphene, etc. have certain conductivity. At high filler content, local conductive paths will be formed in the polyimide coating, resulting in increased leakage current and even breakdown. The interface defects between the filler and the polyimide matrix may also become the starting point of local discharge, further weakening the electrical insulation performance of the coating. As electronic equipment develops towards miniaturization, lightweight and high performance, the requirements for the heat resistance, insulation performance and thermal stability of enameled wire are also getting higher and higher. Therefore, in order to meet these challenges, it is necessary to develop a polyimide enameled wire that has better thermal conductivity while meeting the high heat resistance and high insulation properties of conventional enameled wires. Summary of the invention
[0005] The present invention aims to overcome the deficiencies in the prior art and provides a polyimide enameled wire and a preparation method thereof. The polyimide enameled wire comprises a conductor and a polyimide varnish layer arranged on the conductor, wherein the polyimide insulating varnish layer is formed by heating and curing a polyamic acid solution containing BeO particles and AlN powder. The present invention uses BeO and AlN as inorganic additives of the polyimide varnish layer, which can significantly improve the thermal conductivity of the polyimide insulating layer, improve the heat dissipation performance of the enameled wire, and prevent the enameled wire from being degraded or damaged due to overheating in a high temperature environment. At the same time, the introduction of the two can also improve the electrical insulation performance of the polyimide enameled wire. BeO has a higher breakdown voltage, and AlN can maintain good electrical insulation and mechanical strength of the insulating varnish. At the same time, the expansion coefficients of BeO and AlN are close to those of polyimide. When the temperature of the enameled wire changes greatly, the stress between the inorganic additive particles and the polyimide is small, which can effectively reduce the risk of cracking or peeling of the coating and maintain good interface bonding. In addition, BeO has a higher breakdown voltage, and AlN has good electrical insulation and mechanical strength. The combination of the two can provide double electrical insulation protection for polyimide and maintain more stable electrical insulation performance under high temperature and high voltage environments.
[0006] To achieve the above-mentioned object of the present invention, the first aspect of the present invention provides a polyimide enameled wire, comprising a conductor and a polyimide lacquer layer arranged on the conductor, wherein the polyimide insulating lacquer layer is formed by heating and curing a polyamic acid solution containing BeO particles and AlN powder. Conventional polyimide has a low thermal conductivity. Although the enameled wire using it has a certain strength of high temperature resistance, due to its low thermal conductivity, the heat generated by the conductor cannot be effectively transferred and dissipated, and it is easy to cause the enameled wire to overheat and burn when used for a long time. The thermal conductivity of BeO used in the present invention is 200~330 W / m·K, and the thermal conductivity of AlN is 170~320 W / m·K, which is much higher than that of polyimide. By introducing these two high thermal conductivity additives, the thermal conductivity of polyimide is greatly improved, and the heat dissipation performance of the enameled wire is effectively improved. When the enameled wire is used in high-temperature environments such as high-power motors, transformers, aerospace, etc., the efficient heat dissipation capacity can prevent the performance degradation or damage of the enameled wire due to overheating, which not only extends the service life of the enameled wire, but also improves the overall efficiency and reliability of the equipment.
[0007] Furthermore, the conductor is a copper wire or an aluminum wire, and the thickness of the polyimide insulating varnish layer is 0.01 to 1 mm. Furthermore, the thickness of the polyimide insulating varnish layer may be 0.05 to 0.5 mm; more preferably, the thickness of the polyimide insulating varnish layer may be 0.1 to 0.5 mm. There is no special limitation on the specific thickness value, which is suitable to meet the actual product application scenario.
[0008] Furthermore, the mass ratio of BeO to AlN in the polyimide insulating varnish layer is 1:2-5, and the total filling amount of BeO and AlN is 1%-10% of the weight of the polyimide.
[0009] Furthermore, the BeO particles are spherical particles with an average particle size of 0.1 to 1 μm, and the AlN powder is spherical or flaky particles with an average particle size of 0.01 to 1 μm. For polyimide enameled wire, the morphology and particle size of inorganic additives will significantly affect the electrical insulation and mechanical properties of the enameled wire. The present invention selects spherical BeO particles, which are easier to disperse evenly in the matrix, reduce agglomeration, and reduce the risk of cracking or peeling of the coating. At the same time, the flaky material can form a "heat conduction path" in the matrix, increase the heat conduction path, and significantly improve the thermal conductivity of the composite material. For the effect of the particle size of spherical granular inorganic additives on thermal conductivity, it is generally believed that the smaller the particle size, the more heat conduction paths can be formed in the matrix, and the higher the thermal conductivity of the composite material, but small-sized particles are more likely to agglomerate, which is not conducive to their dispersion in the composite material, but will affect the heat dissipation and insulation performance of the polyimide enameled wire. After a large number of experiments, it was found that when spherical BeO with a relatively large particle size is mixed with spherical or flaky AlN with a relatively small particle size as an inorganic additive, the particles are less aggregated and are evenly dispersed in the polyimide, forming a stable heat transfer path, improving the thermal conductivity of the polyimide, and thus improving the heat dissipation capacity of the enameled wire.
[0010] Furthermore, the polyamic acid solution is prepared by the following method: Step 1: Weigh 0.99 mol to 1.01 mol of dibasic acid anhydride and dissolve it in 1 L of organic solvent, stir and continuously introduce protective gas to obtain solution A; Step 2: Weigh BeO particles and AlN powder, ball-mill until the average particle size of BeO particles is 0.1-1 μm, and the average particle size of AlN powder is 0.01-1 μm, add BeO particles and AlN powder to solution A in sequence, and disperse them for 1-5 hours using a high-speed disperser until they are uniformly dispersed to obtain solution B; Step 3: Weigh 0.98 mol to 1 mol of diamine and dissolve it in solution B. Stir and continuously introduce protective gas. After it is evenly dispersed, react at 50-80°C for 4-12 hours and cool to room temperature to obtain the product.
[0011] Furthermore, the dibasic acid anhydride is at least one of pyromellitic anhydride, 3,3',4,4'-biphenyltetracarboxylic anhydride or 3,3',4,4'-benzophenonetetracarboxylic anhydride; the diamine is at least one of 4,4'-diaminodiphenyl ether, p-phenylenediamine or 4,4'-diaminobenzophenone; and the organic solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide.
[0012] Furthermore, the protective gas is one of nitrogen, helium and argon, the mass ratio of BeO to AlN is 1:2-5, and the total filling amount of BeO and AlN is 1%-10% of the weight of the polyimide.
[0013] Another aspect of the present invention provides a method for preparing a polyimide enameled wire, comprising the following steps: Step 1: Prepare a polyamic acid solution: weigh 0.99 mol to 1.01 mol of a dibasic acid anhydride and dissolve it in 1 L of an organic solvent, stir and continuously introduce a protective gas to obtain a solution A; weigh BeO particles and AlN powder, ball-mill until the average particle size of the BeO particles is 0.1 to 1 μm, and the average particle size of the AlN powder is 0.01 to 1 μm, and sequentially add the BeO particles and AlN powder to solution A, and use a high-speed disperser to disperse for 1 to 5 hours until the dispersion is uniform to obtain a solution B; weigh 0.98 mol to 1 mol of a diamine and dissolve it in solution B, stir and continuously introduce a protective gas, and after uniform dispersion, react at 50 to 80° C. for 4 to 12 hours, and cool to room temperature; Step 2: Immerse the wire in the polyamic acid solution obtained in step 1 for coating, and perform multi-stage heating treatment until the surface of the wire is coated with a polyimide insulating paint layer of a desired thickness.
[0014] Furthermore, the conductive wire is a copper wire or an aluminum wire, and the thickness of the polyimide insulating paint layer is 0.01-1 mm.
[0015] Furthermore, the step 2 is specifically as follows: placing the polyamic acid solution into a fixed container of a pulling coating machine, immersing the wire at a speed of 40 to 60 mm / min, and then lifting it at a speed of 10 to 30 mm / min for coating, placing the coated wire into a tubular furnace, and sequentially keeping it at 70 to 90°C for 2 to 4 hours, keeping it at 140 to 160°C for 40 to 60 minutes, keeping it at 220 to 240°C for 30 minutes to 40 minutes, and keeping it at 280 to 300°C for 30 minutes to 40 minutes.
[0016] The polyimide enameled wire prepared by the present invention has high heat resistance, thermal conductivity and heat dissipation capabilities, and good insulation performance. The polyimide enameled wire is wound into a winding coil for use in motor equipment in high-power or high-temperature environments, and can work stably under long-term high-temperature conditions.
[0017] Compared with the prior art, the technical solution of the present invention has the following beneficial effects: The present invention provides a new polyimide enameled wire composition. The introduction of BeO and AlN significantly improves the thermal conductivity of polyimide, thereby effectively improving the heat dissipation performance of the enameled wire, and can prevent the enameled wire from being degraded or damaged due to overheating in a high temperature environment, which not only prolongs the service life of the enameled wire, but also improves the overall efficiency and reliability of the equipment.
[0018] At the same time, the introduction of BeO and AlN can also improve the electrical insulation performance of polyimide enameled wire. Polyimide itself has good electrical insulation performance, BeO also has a high breakdown voltage (20 ~ 30 kV / mm), and AlN also has high electrical insulation (breakdown voltage 10~15 kV / mm). The simultaneous introduction of the two can effectively ensure that the enameled wire will not leak current or breakdown in a high voltage environment. The combination of the two can provide double electrical insulation protection and provide more stable electrical insulation performance in high temperature and high voltage environments.
[0019] Third, the introduction of inorganic fillers will generally improve the mechanical properties of polyimide. AlN has high mechanical strength and wear resistance. The addition of AlN can enhance the mechanical properties of the polyimide paint layer, making it less likely to crack or peel off during bending, stretching or vibration, thereby extending the service life of the enameled wire. The applicant has also found in a large number of experiments that the selection of inorganic fillers also has certain requirements. If the selection is not appropriate, it will also affect the adhesion ability or film-forming property of the enameled wire on the conductor to a certain extent, such as cracking or peeling of the coating, affecting product performance. The applicant has found through a large number of experiments that the simultaneous introduction of AlN and BeO into polyimide does not cause cracking or peeling of the coating. After analysis, it is believed that the thermal expansion coefficients of the two are close to those of polyimide. When the temperature of the enameled wire changes, the stress between the inorganic substance and the polyimide is small, and good interface bonding can be maintained.
[0020] In addition, both BeO and AlN have extremely high heat resistance. BeO can withstand high temperatures exceeding 1000°C in a short period of time, and the long-term operating temperature of AlN can reach above 300°C. By introducing these two high heat-resistant fillers, the heat resistance of polyimide enameled wire can be significantly improved, enabling it to work stably in extremely high temperature environments and avoid performance degradation due to thermal degradation.
[0021] At the same time, the preparation method of the present application is simple. By dispersing BeO particles and AlN powder in a polyamic acid solution, uniform distribution can be achieved during the coating process, filler agglomeration can be avoided, and the uniformity and consistency of the coating can be ensured. DETAILED DESCRIPTION
[0022] In order to make the technical problems solved by the present invention, the technical solutions adopted and the technical effects achieved clearer, the technical solutions of the embodiments of the present invention are further described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.
[0023] It should be noted that the reference to "embodiment" in this document means that the specific features, structures or characteristics described in conjunction with the embodiment may be included in at least one embodiment of the present application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0024] The experimental methods in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples are commercially available unless otherwise specified.
[0025] Example 1
[0026] A polyimide enameled wire comprises a conductor copper wire and a polyimide lacquer layer with a thickness of 0.01 mm arranged on the copper wire, wherein BeO particles and AlN powder are dispersed in the polyimide insulating lacquer layer. The preparation method of the polyimide enameled wire is as follows: 1) Preparation of polyamic acid solution: weigh 0.99 mol of pyromellitic dianhydride (PMDA) and dissolve it in 1 L of N,N-dimethylformamide, stir and continuously introduce nitrogen to obtain solution A; weigh 1.39 g of BeO spherical particles and 2.78 g of AlN spherical particles, ball-mill until the average particle size of BeO particles is 1 μm and the average particle size of AlN powder is 0.01 μm, add BeO and AlN to solution A in turn, and disperse them for 1 hour using a high-speed disperser until they are uniformly dispersed to obtain solution B; weigh 0.98 mol of 4,4'-diaminodiphenyl ether (ODA) and dissolve it in solution B, stir and continuously introduce nitrogen, react at 50°C for 4 hours after uniform dispersion, and cool to room temperature; 2) Put the polyamic acid solution into the fixed container of the pull coating machine, immerse the copper wire at a speed of 40mm / min, and then lift it at a speed of 10mm / min for coating. Put the coated copper wire into the tube furnace and keep it at 70℃ for 2h, 140℃ for 40min, 220℃ for 30min, and 280℃ for 30min in sequence. Repeat the above operation until the thickness of the polyimide insulating paint layer is 0.01mm. After measurement, the thermal conductivity of the prepared enameled wire is 5.896W / m·K, and it can be used normally at 300℃ without shedding or delamination.
[0027] Example 2
[0028] A polyimide enameled wire comprises an aluminum wire and a polyimide varnish layer disposed on the aluminum wire, wherein BeO particles and AlN powder are dispersed in the polyimide insulating varnish layer. The preparation method of the polyimide enameled wire is as follows: 1) Preparation of polyamic acid solution: 1.01 mol of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) was weighed and dissolved in 1L N,N-dimethylacetamide, stirred and continuously introduced helium to obtain solution A; 7.1 g of BeO spherical particles and 35.5 g of AlN flake particles were weighed and ball-milled until the average particle size of the BeO particles was 0.1 μm and the average particle size of the AlN powder was 0.05 μm, and the ball-milled BeO and AlN were added to solution A in turn, and dispersed for 5 hours using a high-speed disperser until the dispersion was uniform to obtain solution B; 1 mol of p-phenylenediamine (PPD) was weighed and dissolved in solution B, stirred and continuously introduced helium, and after uniform dispersion, the mixture was reacted at 80°C for 12 hours and cooled to room temperature; 2) Put the polyamic acid solution into the fixed container of the Czochralski coating machine, immerse the aluminum wire at a speed of 60mm / min, and then lift it at a speed of 30mm / min for coating. Put the coated wire into the tubular furnace and keep it at 90℃ for 4h, 160℃ for 60min, 240℃ for 40min, and 300℃ for 40min in sequence. Repeat the above operation until the thickness of the polyimide insulating paint layer is 1mm. The thermal conductivity of the prepared enameled wire is measured to be 25.36W / m·K, and it can be used for a long time at 300℃ without shedding or delamination.
[0029] Example 3
[0030] A polyimide enameled wire comprises a copper wire and a polyimide varnish layer arranged on the copper wire, wherein BeO particles and AlN powder are dispersed in the polyimide insulating varnish layer. The preparation method of the polyimide enameled wire is as follows: 1) Preparation of polyamic acid solution: 1.0 mol of 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA) was weighed and dissolved in 1 L of N-methylpyrrolidone, stirred and continuously introduced argon to obtain solution A; 5.98 g of BeO spherical particles and 23.94 g of AlN flake particles were weighed and ball-milled until the average particle size of the BeO particles was 0.5 μm and the average particle size of the AlN powder was 0.1 μm, and the ball-milled BeO and AlN were added to solution A in turn, and dispersed for 3 hours using a high-speed disperser until the dispersion was uniform to obtain solution B; 1 mol of 4,4'-diaminobenzophenone (DBA) was weighed and dissolved in solution B, stirred and continuously introduced argon, and after uniform dispersion, reacted at 60°C for 10 hours, and cooled to room temperature; 2) Put the polyamic acid solution into the fixed container of the pull coating machine, immerse the copper wire at a speed of 50mm / min, and then lift it at a speed of 20mm / min for coating. Put the coated wire into the tube furnace and keep it at 80℃ for 3h, 150℃ for 50min, 230℃ for 40min, and 300℃ for 40min in sequence. Repeat the above operation until the thickness of the polyimide insulating paint layer is 0.5mm. After measurement, the thermal conductivity of the prepared enameled wire is 12.88W / m·K, and it can be used for a long time at 300℃ without shedding or delamination.
[0031] Example 4
[0032] A polyimide enameled wire comprises a copper wire and a polyimide varnish layer arranged on the copper wire, wherein BeO particles and AlN powder are dispersed in the polyimide insulating varnish layer. The preparation method of the polyimide enameled wire is as follows: 1) Preparation of polyamic acid solution 1: Weigh 1.0 mol of 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA) and dissolve it in 1 L of N-methylpyrrolidone, stir and continuously introduce argon to obtain solution A; weigh 5.98 g of BeO spherical particles and 23.94 g of AlN flake particles, ball-mill until the average particle size of BeO particles is 0.5 μm and the average particle size of AlN powder is 0.1 μm, add the ball-milled BeO and AlN to solution A in turn, use a high-speed disperser to disperse for 3 hours, and obtain solution B until the dispersion is uniform; weigh 1 mol of 4,4'-diaminobenzophenone (DBA) and dissolve it in solution B, stir and continuously introduce argon, react at 60°C for 10 hours after the dispersion is uniform, and cool to room temperature; 2) Preparation of polyamic acid solution 2: Weigh 1.0 mol of 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA) and dissolve it in 1 L of N-methylpyrrolidone, stir and continuously introduce argon to obtain solution A; weigh 10.48 g of BeO spherical particles and 31.43 g of AlN flake particles, ball-mill until the average particle size of BeO particles is 0.35 μm and the average particle size of AlN powder is 0.08 μm, add the ball-milled BeO and AlN to solution A in turn, and use a high-speed disperser to disperse for 3 hours until the dispersion is uniform to obtain solution B; weigh 1 mol of 4,4'-diaminobenzophenone (DBA) and dissolve it in solution B, stir and continuously introduce argon, react at 60°C for 10 hours after uniform dispersion, and cool to room temperature; 3) Put the polyamic acid solution 1 into a fixed container of the pulling coating machine, immerse the copper wire at a speed of 50 mm / min, and then lift it at a speed of 20 mm / min for coating. Put the coated wire into a tube furnace and keep it at 80°C for 3 hours, 150°C for 50 minutes, 230°C for 40 minutes, and 300°C for 40 minutes in sequence. Repeat the above operation until the thickness of the polyimide insulating paint layer 1 is 0.25 mm; 4) Put the polyamic acid solution 2 into a fixed container of the pulling coating machine, immerse the copper wire coated with a 0.25 mm polyimide insulating paint layer 1 at a speed of 50 mm / min, and then lift it at a speed of 20 mm / min for coating. Put the coated wire into a tubular furnace and keep it at 80°C for 3 hours, 150°C for 50 minutes, 230°C for 40 minutes, and 300°C for 40 minutes in sequence. Repeat the above operation until the thickness of the polyimide insulating paint layer 2 is 0.25 mm; The thermal conductivity of the prepared enameled wire was measured to be 15.76 W / m·K, and it can be used for a long time at 300°C without shedding or delamination. The heat dissipation of the enameled wire is better than that of a single layer.
[0033] Comparative Example 1 A polyimide enameled wire comprises a copper wire and a polyimide varnish layer arranged on the copper wire, wherein BeO particles are dispersed in the polyimide insulating varnish layer. The preparation method of the polyimide enameled wire is as follows: 1) Preparation of polyamic acid solution: 1.0 mol of 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA) was weighed and dissolved in 1 L of N-methylpyrrolidone, stirred and continuously introduced argon to obtain solution A; 30 g of BeO spherical particles were weighed and ball-milled to an average particle size of 1.5 μm, then added to solution A and dispersed for 3 hours using a high-speed disperser until the particles were uniformly dispersed to obtain solution B; 1 mol of 4,4'-diaminobenzophenone (DBA) was weighed and dissolved in solution B, stirred and continuously introduced argon, and after uniform dispersion, the mixture was reacted at 60°C for 10 hours and cooled to room temperature; 2) Put the polyamic acid solution into the fixed container of the pull coating machine, immerse the copper wire at a speed of 50mm / min, and then lift it at a speed of 20mm / min for coating. Put the coated wire into the tubular furnace and keep it at 80℃ for 3h, 150℃ for 50min, 230℃ for 40min, and 300℃ for 40min in sequence. Repeat the above operation until the thickness of the polyimide insulating paint layer is 0.5mm. According to the measurement, the thermal conductivity of the prepared enameled wire is 14.59W / m·K, which can be used for a short time at 300℃, but when the time exceeds 10h, local enameled wire bulging and cracks will appear, and the enameled wire will be partially separated from the copper wire.
[0034] Comparative Example 2 A polyimide enameled wire comprises a copper wire and a polyimide varnish layer arranged on the copper wire, wherein flaky AlN powder is dispersed in the polyimide insulating varnish layer. The preparation method of the polyimide enameled wire is as follows: 1) Preparation of polyamic acid solution: Weigh 1.0 mol of 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA) and dissolve it in 1 L of N-methylpyrrolidone, stir and continuously introduce argon to obtain solution A; weigh 5.98 g of BeO spherical particles and 30 g of AlN flake particles, ball-mill them to an average particle size of 1 μm, add the ball-milled AlN to solution A, and use a high-speed disperser to disperse it for 5 hours until it is uniformly dispersed to obtain solution B; weigh 1.2 mol of 4,4'-diaminobenzophenone (DBA) and dissolve it in solution B, stir and continuously introduce argon, react at 90°C for 2 hours after uniform dispersion, and cool to room temperature; 2) Put the polyamic acid solution into the fixed container of the pull coating machine, immerse the copper wire at a speed of 70mm / min, and then lift it at a speed of 40mm / min for coating. Put the coated wire into the tube furnace and keep it at 300℃ for 5h. Repeat the above operation until the thickness of the polyimide insulating paint layer is 0.5mm. The thermal conductivity of the prepared enameled wire is 10.21W / m·K. It can only be used for a short time at 300℃. When used for a long time, part of it will bulge.
[0035] Comparative Example 3 A polyimide enameled wire comprises a copper wire and a polyimide varnish layer arranged on the copper wire, wherein graphene nanosheets, aluminum oxide and boron nitride are dispersed in the polyimide insulating varnish layer. The preparation method of the polyimide enameled wire is as follows: 1) Weigh 50 parts of polyimide resin, 2 parts of graphene nanosheets, 2 parts of aluminum oxide, and 1 part of boron nitride; dissolve the polyimide resin in an appropriate amount of DMAc to form a solution; add graphene nanosheets, aluminum oxide powder, and boron nitride powder thereto, and stir at high speed until they are evenly dispersed; 2) The copper wire is soaked in the solution obtained in step 1, and then the copper wire is subjected to high temperature treatment and is kept at 40°C, 80°C, and 120°C for 3 hours each, and 240°C and 280°C for 2 hours each, to finally obtain a polyimide enameled wire. According to the measurement, the thermal conductivity of the prepared enameled wire is only 1.43W / m·K, which is improved compared with pure polyimide, but the insulation performance is significantly reduced, and it cannot be used at 300°C, and can barely be used at 240°C.
[0036] The above is a detailed introduction to a polyimide enameled wire and its preparation method. The above content is a further detailed description of the present invention in combination with a specific preferred embodiment, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, without departing from the concept of the present invention, its architecture can be flexible and can derive a series of products. Just making a few simple deductions or substitutions should be regarded as belonging to the scope of patent protection of the present invention determined by the submitted claims.
Claims
1. A polyimide enameled wire, comprising a conductor and a polyimide lacquer layer arranged on the conductor, characterized in that: The polyimide insulating varnish layer is formed by heating and curing a polyamic acid solution containing BeO particles and AlN powder.
2. The polyimide enameled wire according to claim 1, characterized in that: The conductor is a copper wire or an aluminum wire, and the thickness of the polyimide insulating paint layer is 0.01-1 mm.
3. The polyimide enameled wire according to claim 1, characterized in that: The mass ratio of BeO to AlN in the polyimide insulating varnish layer is 1:2-5, and the total filling amount of BeO and AlN is 1%-10% of the weight of the polyimide.
4. The polyimide enameled wire according to claim 1, characterized in that: The BeO particles are spherical particles with an average particle size of 0.1-1 μm, and the AlN powder is spherical or flaky particles with an average particle size of 0.01-1 μm.
5. The polyimide enameled wire according to claim 1, characterized in that: The polyamic acid solution is prepared by the following method: Step 1: Weigh 0.99 mol to 1.01 mol of dibasic acid anhydride and dissolve it in 1 L of organic solvent, stir and continuously introduce protective gas to obtain solution A; Step 2: Weigh BeO particles and AlN powder, ball-mill until the average particle size of BeO particles is 0.1-1 μm, and the average particle size of AlN powder is 0.01-1 μm, add BeO particles and AlN powder to solution A in sequence, and disperse them for 1-5 hours using a high-speed disperser until they are uniformly dispersed to obtain solution B; Step 3: Weigh 0.98 mol to 1 mol of diamine and dissolve it in solution B. Stir and continuously introduce protective gas. After it is evenly dispersed, react at 50-80°C for 4-12 hours and cool to room temperature to obtain the product.
6. The polyimide enameled wire according to claim 5, characterized in that: The dibasic acid anhydride is at least one of pyromellitic acid anhydride, 3,3',4,4'-biphenyltetracarboxylic acid anhydride or 3,3',4,4'-benzophenonetetracarboxylic acid anhydride; the diamine is at least one of 4,4'-diaminodiphenyl ether, p-phenylenediamine or 4,4'-diaminobenzophenone; and the organic solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and dimethyl sulfoxide.
7. The polyimide enameled wire according to claim 5, characterized in that: The protective gas is one of nitrogen, helium and argon. The mass ratio of BeO to AlN is 1:2-5. The total filling amount of BeO and AlN is 1%-10% of the weight of the polyimide.
8. A method for preparing a polyimide enameled wire according to any one of claims 1 to 4, characterized in that: The steps include: Step 1: Prepare a polyamic acid solution: weigh 0.99 mol to 1.01 mol of a dibasic acid anhydride and dissolve it in 1 L of an organic solvent, stir and continuously introduce a protective gas to obtain a solution A; weigh BeO particles and AlN powder, ball-mill until the average particle size of the BeO particles is 0.1 to 1 μm, and the average particle size of the AlN powder is 0.01 to 1 μm, and sequentially add the BeO particles and AlN powder to solution A, and use a high-speed disperser to disperse for 1 to 5 hours until the dispersion is uniform to obtain a solution B; weigh 0.98 mol to 1 mol of a diamine and dissolve it in solution B, stir and continuously introduce a protective gas, and after uniform dispersion, react at 50 to 80° C. for 4 to 12 hours, and cool to room temperature; Step 2: Immerse the wire in the polyamic acid solution obtained in step 1 for coating, and perform multi-stage heating treatment until the surface of the wire is coated with a polyimide insulating paint layer of a desired thickness.
9. The method for preparing a polyimide enameled wire according to claim 8, characterized in that: The conductor is a copper wire or an aluminum wire, and the thickness of the polyimide insulating paint layer is 0.01-1 mm.
10. The method for preparing a polyimide enameled wire according to claim 9, characterized in that: The step 2 is specifically as follows: putting the polyamic acid solution into a fixed container of the pulling coating machine, immersing the wire at a speed of 40 to 60 mm / min, and then lifting it at a speed of 10 to 30 mm / min for coating, putting the coated wire into a tubular furnace, and sequentially keeping it at 70 to 90° C. for 2 to 4 hours, keeping it at 140 to 160° C. for 40 to 60 minutes, keeping it at 220 to 240° C. for 30 minutes to 40 minutes, and keeping it at 280 to 300° C. for 30 minutes to 40 minutes.
Citation Information
Patent Citations
Manufacturing method of enameled wire with radiating function
CN102385957A
Cooling system of enameled wire
CN104934145A
220 grade polyimide enameled copper round wire and its production process
CN111326287B
Enameled rectangular wire with high heat dissipation efficiency and production process thereof
CN115810449A
High-thermal-conductivity insulating copper flat wire for 10kV high-voltage motor and preparation method of high-thermal-conductivity insulating copper flat wire
CN116313274A
Cited By
High-strength and high-elongation aluminum-clad steel core aluminum alloy stranded wire and preparation method thereof
CN120809327A